APPROACHES TO THE ANALYSIS AND EVALUATION OF URBAN TOURISM SYSTEM WITHIN URBAN DESTINATIONS - BĂDIŢĂ, Amalia (Revista de turism - studii și cercetări în turism, 2013)
The city is an area that has a complex functionality which is based on the utility of its zones that imprint a quality of life and a specificity to the place, but it is also based on the architectural aesthetics which determines a local lifestyle and a potential which can be exploited through tourist activities. The study aims to identify the characteristics of the urban tourism and the elements of an urban tourism system, which will be approached by identifying the city-breaker profile, the relation between turisticity and urbanity to determine the quality of places. These elements will be applied as a case study in Craiova, a mixed industrial and services economical profile city, with a low tourism function. This type of city has an urban tourism system which starts to take shape, and according to the theory of "overlapping cities" although there are many forms of tourism in a city (cultural, business, shopping, sports tourism, visiting relatives and friends and recreational tourism), Craiova focuses on the typology of the city for festivals, business, leisure and sport, as a strategy for the tourism sector development and for entering the tourism market of Romania.